(3eYQaI ChGFd GdSfjf GdbHWjI hChGFd TghQgGs
(3ChdgG (B:s
(3hgh Cf JMPa EeG YTQ ef CMO hKdGKjf HYO GdCda , hGdHGbi ef CMO hKdGKjf JRjO Ydjg QHYg HZjQ cSQ s
(3BNQgG (B:s
(3aeG NQL ddbSe GdhGMO GVQHg ai Xd QCSi GdGYJOGdjf HPdc GdHdO aeG NQL jchf GdeWdhH JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3482(1)) s
Keywords: (3Gdadcs